Investigating Metacognitive Strategies for overcoming Barriers to Reading Comprehension: Insights from a Pakistani Context - Channa Mansoor Ahmed; Abassi Abdul Malik; Nordin Zaimuariffudin Shukri; Muhammad Jam Khan; Arain Rubina Shaheen (Journal of Language and Cultural Education, 2018)
The main aim of this research was to investigate metacognitive strategies through reading comprehension practice by first year students of engineering departments. The students of four engineering departments were selected as the participants in this research work. The qualitative instrument based on focus group interview was used for collecting data from first year students of four engineering departments to know the perceptions and their needs to develop reading comprehension through metacognitive strategies. The researchers developed interview questions for this study. These questions were validated by two experts of faculty of cognitive science and human development at university Malaysia Sarawak. The researchers obtained permission from the chairmen of four departments at a university in Pakistan. Almost 8 groups consisting of 5 informants in each participated in this research. The data was documented by using audio-tape; NVivo software, version 8 was used to organize data for obtaining main themes of the study. This research generated the most important themes for the interpretation of the results. The study contributed the most promising results which revealed that more than half of these groups used metacognitive strategies in classroom reading practice while less than half of groups did not use strategies and remained poor in reading comprehension. This research suggested administrators, teachers, and curriculum designers to design and implement reading comprehension courses and syllabus for first year engineering students.